Dividend Announcement Effect To Market Reaction in Non-Financial Companies Listed on Indonesia Stock Exchange - Alvin Fabian; Eko Budi Santoso (JOURNAL OF ACCOUNTING, ENTREPRENEURSHIP AND FINANCIAL TECHNOLOGY (JAEF), 2020)
Abstract: This study aims to examine the differences in market reaction before and after the announcement of dividend omissions and dividend initiations in non- financial companies listed on the Indonesia Stock Exchange in 2016-2018. The sample used in this study was 71 companies consisting of 26 companies that announced dividend omissions and 45 companies that announced dividend initiations. The sample was determined using the purposive sampling method. This study used the event study method with an event window period of 5 days before the announcement, the announcement day, and 5 days after the announcement. The Wilcoxon Signed Ranks Test results in this study indicate that there are no differences in market reaction before and after the announcement of dividend omissions. Meanwhile the announcement of dividend initiations shows that there are differences in market reaction before and after the announcement of dividend initiations. Keywords: Event study, Dividend Omissions, Dividend Initiations, Abnormal Return